2006
DOI: 10.1088/0268-1242/21/8/027
|View full text |Cite
|
Sign up to set email alerts
|

Singularities in the magneto-photoluminescence spectra from isolated quantum dots

Abstract: We have optically investigated quantum dots containing a few electrons each. In zero magnetic field, the photoluminescence (PL) should reflect the occupied density of states of such artificial atoms. However, the few-electron response to recombination of one of these electrons with a localized hole appears to be enhanced as the energy of the electrons approaches the highest occupied state. This phenomenon resembles the Fermi-edge singularity observed in the PL spectra from n-type two-and one-dimensional electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The real geometry of self-assembled In(Ga)As quantum dots grown on GaAs substrates is rather complicated. For example, Kiravittaya et al [27] reported two types of QD shapes: pyramids elongated along the [1][2][3][4][5][6][7][8][9][10] directions bounded by [137] facets, and domes with a multi-faceted shape. However, we approximate the specific In 0.5 Ga 0.5 As self-assembled quantum dot with a lens-shaped potential (figure 1).…”
Section: Comparison With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The real geometry of self-assembled In(Ga)As quantum dots grown on GaAs substrates is rather complicated. For example, Kiravittaya et al [27] reported two types of QD shapes: pyramids elongated along the [1][2][3][4][5][6][7][8][9][10] directions bounded by [137] facets, and domes with a multi-faceted shape. However, we approximate the specific In 0.5 Ga 0.5 As self-assembled quantum dot with a lens-shaped potential (figure 1).…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…Photoluminescence (PL) is a powerful tool for the understanding of the QDs characteristics and it has been intensively studied in recent years both experimentally [2][3][4][5] and theoretically [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%